Reconfigurable intelligent surfaces as the key-enabling technology for smart electromagnetic environments - F. Bilotti; M. Barbuto; Z. Hamzavi-Zarghani; M. Karamirad; M. Longhi; A. Monti; D. Ramaccia; L. Stefanini; A. Toscano; S. Vellucci (Advances in Physics: X)
Future wireless systems integrating communication and sensing will require handling an enormous amount of data with extremely low latency. Intense video streaming data traffic, pervasive-augmented and virtual reality services, advanced haptic–tactile interaction and holography-type communications, in fact, reveal a trend towards experience-based networks and multi-sense media, which require seamless connectivity and ultra-high capacity. Using current 5G technologies to take mentioned challenges, might not represent the desired solution and a completely new paradigm is needed. Recently, to support this change, scientists have been focusing on the concept of Smart Electromagnetic Environments (SEE), based on deploying a number of smart nodes, whose electromagnetic response needs to be finely adapted to the changing operative conditions. In this framework, a pivotal role is played by reconfigurable intelligent metasurfaces, allowing the implementation of smart skins, reflecting intelligent surfaces, smart repeaters, and intelligent antennas. This paper aims at offering an insightful review of the role of intelligent metasurfaces in advancing the concept of SEE. Different application domains will be illustrated: advanced signal processing at the physical layer, a new generation of smart antennas whose intelligence is enabled by the physical layer, and practical implementation of reflecting intelligent surfaces. With an in-depth analysis of these areas, this review sheds light on how intelligent metasurfaces drive innovation in wireless communication shaping the future of SEEs.